The impact of financialdepth on the effectiveness of monetary policy in Algeria an econometric study for the period 1990-2019 - dardour, asma (Journal of Research in Finance and Accounting, 2022)
The study aims to determine the impact of financial depth on the effectiveness of monetary policy in algeria during the period (1990-2019) use ARDL model. Were used an independent variables representing financial depth (cppib, deppib, m2pib) and the dependent variable represented in the GDP. The long-term results reflect the negation of the study hypothesis that the financial depth represented by each of its indicators( cppib, m2 pib) will support the effectiveness of monetary policy, which shows the negative impact of financial depth in Algeria on the effectiveness of monetary policy by affecting GDP, while the deppib index supports the hypothesis of the study that increasing financial depth enhances the effectiveness of monetary policy and GDP growth.